Evaluation of p-Naphtholbenzein-β-d-Galactoside as a Substrate for Bacterial β-Galactosidase - James, A. L. (American Society for Microbiology, 2000)
We describe the synthesis of a new substrate for the detection of β-galactosidase and evaluate its performance in comparison with 5-bromo-4-chloro-3-indolyl-β-d-galactopyranoside (X-Gal) and cyclohexenoesculetinβ-d-galactoside (CHE-Gal). Of 206 Enterobacteriaceae strains able to hydrolyze X-Gal, 194 (94.2%) hydrolyzed CHE-Gal and 192 (93.2%) hydrolyzed p-naphtholbenzein-β-d-galactoside (PNB-Gal). We conclude that PNB-Gal is an effective substrate for the detection of β-galactosidase.